Maternal, socioeconomic and healthcare factors associated with postpartum maternal mortality in Papua Province, Indonesia, based on secondary data analysis of IDHS 2020 - Safitri, Dian Laily; Handayani, Samsriyaningsih; Prasetyo, Budi; Jayanti, Ratna Dwi (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Postpartum maternal mortality demonstrates associations with determinants including parity, place of residence, proficiency in the Indonesian language, socioeconomic status or wealth index, type of delivery attendant, and place of childbirth. Proficiency in the Indonesian language constitutes the most dominant factor, plausibly indicating inequalities in healthcare access, levels of health literacy, and conditions of geographic or social marginalization.   ABSTRACT Objective: This study utilized data from the Indonesia Demographic Health Survey (IDHS) 2020 to examine the relationship between postpartum maternal mortality and several determinants, including maternal, socioeconomic, and healthcare-related factors in Papua Province. Materials and Methods: A cross-sectional design with a quantitative analytical framework was applied, drawing on secondary data from IDHS 2020. The sample comprised 14,802 women aged 15–49 years. Data were analyzed through a simple logistic regression test for bivariate analysis with a 95% confidence level (a = 0.05). Subsequently, multivariate multiple logistic regression analysis was conducted on variables with a p-value of less than 0.25. Results: Findings demonstrated that all variables (parity p<0.001 AOR=0.533 95% CI 0.375–0.758; place of residence p=0.001 AOR=2.526 95% CI 1.438–4.436; proficiency in Indonesian language p<0.001 AOR=0.039 95% CI 0.031–0.050; delivery attendant and place of birth p<0.001 AOR=0.118 95% CI 0.142–0.249, whereas wealth index status p=0.972 AOR=1.010 95% CI 0.565–1.806) showed a significant negative association with postpartum maternal mortality (p<0.05), except for the wealth index. The strongest association, with an odds ratio (OR) of 0.039, was identified in Indonesian language proficiency, indicating a 25.64-fold increase. Conclusion: The findings provide a crucial evidence base for the development of policies and interventions aimed at lowering postpartum maternal mortality in Papua Province. Proficiency in the Indonesian language emerged as the most influential factor, underscoring the potential for targeted interventions and improved healthcare outcomes.